2022
DOI: 10.3390/ijerph192013252
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Risk for Dengue Infection Mediates the Relationship between Attitude and Practice for Dengue Prevention: A Study in Seremban, Malaysia

Abstract: Dengue remains a public health concern due to limited curative treatment and safe vaccine availability. Prevention by individual is utmost necessary but its practice is still lacking. Perceived risk to disease has been reported to exert a good effect on health behaviour change. However, limited evidence showed its relationship towards attitude and practice for dengue prevention. Hence, we aim to measure the mediating effect of dengue risk perception in the relationship between dengue attitude and dengue preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Moreover, our study found that preventative measures were frequently practised by those who considered removing mosquito breeding sites as their own responsibility, who were, in turn, those with previous history of DF, similar to past studies [ 16 , 47 ]. This suggests a lack of motivation to change current behaviour/habits, unless individuals experience and fully perceive the risks of DF [ 18 , 41 , 45 , 48 ]. Therefore, we recommend these strategies for government agencies and non-governmental organisations (NGOs):…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, our study found that preventative measures were frequently practised by those who considered removing mosquito breeding sites as their own responsibility, who were, in turn, those with previous history of DF, similar to past studies [ 16 , 47 ]. This suggests a lack of motivation to change current behaviour/habits, unless individuals experience and fully perceive the risks of DF [ 18 , 41 , 45 , 48 ]. Therefore, we recommend these strategies for government agencies and non-governmental organisations (NGOs):…”
Section: Discussionmentioning
confidence: 99%
“…The selected models were used to create an overarching model via piecewise structural equation modelling (PSEM) [ 18 , 19 , 24 , 34 ], using ‘psem()’ from the ‘piecewiseSEM’ package [ 35 ]. Based on the linear mixed-effects modelling results, ‘Knowledge’, ‘Attitude’ and ‘Practice’ were considered to be correlated rather than directly causally associated, and therefore were indicated as correlated errors in the PSEM.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies conducted in Indonesia and Colombia have shown that adults who have experienced dengue are also more likely to have a positive attitude toward preventing it [55,56]. In terms of the impact of dengue experience on prevention practices, a study from Malaysia found age and dengue history are the main determinants that influence a high practice level [57], which is consistent with another study's result where previous dengue infections were positively associated with dengue prevention practices [58]. Therefore, if a child had a previous dengue infection, it is likely that this experience improved the overall KAP in the household [52,58].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%